Implementasi Pembacaan Al-Ma’tsurat dalam Pembentukan Karakter Religius di Sekolah Dasar Islam - Muhammad Iqbal Ansari; Nur Annisa; Sari Kumala (IAI Al Khoziny Buduran Sidoarjo, 2022)
This journal tries to illustrate how Al-Ma'tsurat is taught in Islamic elementary schools and how reading it helps students develop their religious character.The principal, student representative, homeroom teacher, and students are the subjects of this case study, which employs a qualitative methodology. gathering information via observation, conversation, and documentation. Data reduction, data presentation, and data verification are all types of data analysis procedures.Source triangulation and technical triangulation are also used to determine the authenticity of the data. Based on the results of the study, it can be concluded that the implementation of reading Al-Ma'tsurat in Islamic elementary schools is carried out by: 1) Planning, 2) Implementation, and 3) Evaluation. The formation of religious character through the reading of Al-Ma'tsurat in Islamic elementary schools is carried out with an approach to the formation of religious characters, namely: 1) Exemplary, 2) Habituation, 3) Instilling Discipline, and 4) Creating a conducive atmosphere. This is also accompanied by the achievement of indicators of religious character, including obedience, gratitude, sincerity, patience, shame in making mistakes, soft-hearted, tolerant, love of knowledge and happy to learn something, and honest.